Antidiabetic Activity of Lupeol and Lupeol Esters in Streptozotocin- Induced Diabetic Rats - Lakshmi, Vijai; Mahdi, Abbas Ali; Ahmad, Mohammad Kaleem; Agarwal, Santosh Kumar; Srivastava, Arvind Kumar (Bangladesh Pharmaceutical Journal, 2015)
Currently, natural products have been shown to present interesting biological and pharmacological activities and are also used as chemotherapeutic agents. Plants have been used in treating cancer, cardiovascular disorders, tuberculosis and many other diseases. Therefore, the current study was designed to evaluate the antidiabetic potential of lupeol and its semisynthetic derivatives to get a new and potent antidiabetic agent. The ethanol extract of Crataeva nurvala, its hexane and chloroform soluble fractions and lupeol isolated from the extractives were evaluated.. Lupeol derivatives were prepared through a one-step reaction with acid chlorides, long chain fatty acids and aromatic moieties. A series of ester derivatives of lupeol were assayed for antidiabetic activity in (STZsucrose model rats. Few derivatives of lupeol showed more potent activity as compared to the basic molecule, lupeol. The results of the present study clearly indicated that the ethanol extract, fractions and lupeol isolated from C. nurvala and synthetic lupeol analogs possess significant antidiabetic activity. The models used for studying theantidiabetic activities have already been validated. In our studies, it was found that the ester derivatives of lupeol posses better antidiabetic potential when compared to lupeol. It is thus concluded that lupeol skeleton deserves further investigation for the development of more potent and non-toxic new antidiabetic agents for therapeutic applications. DOI: http://dx.doi.org/10.3329/bpj.v17i2.22330 Bangladesh Pharmaceutical Journal 17(2): 138-146, 2014